124I-PET/CT images of differentiated thyroid cancer patients - Rosenbaum-Krumme, S.; Nagarajah, J.; Ruhlmann, M.; Bockisch, A.; Jentzen, W. (Nuklearmedizin - NuclearMedicine, 2012)
For an adequate therapy planning and staging of patients with differentiated thyroid cancer (DTC), the correct assignment of thyroid remnants (TRs) and lymph node metastases (LMs) is important. Patients, method: We retrospectively analyzed whether kinetic quantities can help improving LM assignment using serial 124I-PET/CT data. 127 patients with a total of 317 lesions (TR: n = 265; LM: n = 52) received pre-therapy 124I-PET/CT lesion dosimetry using images 24 h and > 96 h after 124I administration. For each lesion, maximum activity concentration (MAC) at 24 h and effective half-life (EHL) were determined. Moreover, the product of MAC and EHL was also investigated as a quantity and is referred to CAQ (cumulated activity proportional quantity). In addition, differences between endogenous and exogenous thyroid-stimulating hormone (TSH) stimulation and between papillary (PTC) and follicular thyroid cancer (FTC) were investigated. Results, conclusion: The median MAC, EHL, and CAQ values in TR were significantly higher than in LM but a clinically relevant cut-off value could not be determined because of high overlapping regions. No significant differences for the three quantities were found for the mode of TSH stimulations, but a significant difference for MAC and CAQ between PTC and FTC.
Keywords: Differentiated thyroid carcinoma; iodine-124; PET; PET/CT; iodine kinetics